(3UMGaI GdGWaGd aj GdLRGFQ (B:s (3OQGSI aj JMdjd GdeVehf GdLRA GdGhd (B( 1962-1982) /s - (3ThJQj, CMeOs ((3GdLRGFQ (B:s (3WGcSjL(B.(3ce ,s, 2011)
(3JJdNU eTcdI GdHMK aj GdJYQa Ydi UMGaI GdGWaGd aj GdLRGFQ aj GdaJQI GdeMOOI h Pdc NdGd HMK GdLhGfH GdJGQjNjI GVGaI Gdi GMUGA h JMdjd eVehf gPg GdUMGaI h eYGjfI LhGfH GdJbOe GdPj GMQRJg gPg GdUMGaI h GdUYhHGJ h GdeTGcd GdJj GYJQVJgG ceG jgOa gPG GdHMK GdiVHW h JMOjO UMGaI GdGWaGd GdhWfjI aj GdLRGFQ h GdeQGMd GdJj eQJ HgG h WHjYI GdeDSSGJ GdJGHYI dgG h NUGFUgG h YdGbJgG HGdeLJeY h eDSSGJ GdOhdI h eOi eSGgeJgG aj eLGd GdJQHjI s
Keywords: (3JMdjd GdeVehfs; (3GdUMGaIs